Effect of the CYP3A inhibitors, diltiazem and ketoconazole, on ticagrelor pharmacokinetics in healthy volunteers. (2nd April 2013) - Teng, Renli; Butler, Kathleen
Abstract: Objectives: Two open-label, two-period, crossover studies in healthy volunteers were designed to determine the pharmacokinetic interactions between ticagrelor, a P2Y12 receptor antagonist, and a moderate (diltiazem) and a strong (ketoconazole) cytochrome P450 (CYP) 3A inhibitor. Methods: Seventeen volunteers received diltiazem (240 mg once daily) for 14 days. In the second study, ketoconazole ( n  = 14) 200 mg twice daily was given for 10 days. A single oral 90-mg ticagrelor dose was administered on day 8 (diltiazem) or day 4 (ketoconazole). In each study, volunteers received a single 90-mg oral dose of ticagrelor before or after washout (≥14 days). Pharmacokinetic parameters for ticagrelor, AR-C124910XX (primary metabolite), diltiazem, and ketoconazole were assessed. Results: Compared with ticagrelor alone, diltiazem co-administration significantly increased the mean maximum concentration ( C max ) and mean area under the plasma concentration–time curve (AUC) for ticagrelor by 69% and 174%, respectively. Diltiazem co-administration reduced C max by 38% but had no significant effect on AUC for AR-C124910XX. C max and AUC for ticagrelor were increased by 135% and 632%, respectively, by ketoconazole co-administration, whereas these parameters were reduced by 89% and 56%, respectively, for AR-C124910XX. Diltiazem and ketoconazole pharmacokinetic parameters were not significantly affected by the presence of ticagrelor. Conclusions: These results suggest that ticagrelor can be co-administered with moderate CYP3A inhibitors. However, co-administration of strong CYP3A inhibitors with ticagrelor is not recommended.